2016
DOI: 10.2486/indhealth.2015-0195
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between depressive symptoms and perceived individual level occupational stress among Japanese schoolteachers

Abstract: Japanese teachers are mentally and physically burdened with various work stressors. This cross-sectional study examined the relationship between depressive symptoms and perceived individual level occupational stress including role problems among Japanese schoolteachers. This study included 1,006 teachers working in public schools in a Japanese city. The Japanese version of Zung’s Self-Rating Depression Scale (SDS) was used to evaluate depressive symptoms, and the Generic Job Stress Questionnaire was used to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 20 publications
3
32
3
1
Order By: Relevance
“…Among the 920,760 teachers in Japan, 7796 public school teachers took sick leave in 2018, of which 5077 (65.1%) were diagnosed with mental health disorders [ 7 ]. The present study confirms that workload stressors negatively affect the mental health of high school teachers in Japan [ 8 , 14 , 36 – 38 ], and this is true in other countries as well [ 39 – 41 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Among the 920,760 teachers in Japan, 7796 public school teachers took sick leave in 2018, of which 5077 (65.1%) were diagnosed with mental health disorders [ 7 ]. The present study confirms that workload stressors negatively affect the mental health of high school teachers in Japan [ 8 , 14 , 36 – 38 ], and this is true in other countries as well [ 39 – 41 ].…”
Section: Discussionsupporting
confidence: 86%
“…Occupational stressors are one factor having a negative impact on the mental health of teachers. According to existing research, some of the stressors that affect the mental health of teachers are job content stress [ 8 ], long working hours [ 9 ], job dissatisfaction [ 10 – 12 ], interpersonal conflict at work [ 13 , 14 ], conflict with students and parents [ 13 ], and high job demands with low job management [ 15 , 16 ]. However, most of these existing studies have focused on primary school and junior high school teachers, with few focusing on high school teachers [ 9 , 11 , 12 , 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This report indicated that Japanese teachers spend substantially more time on other tasks related to their job than they spend actually teaching. We previously reported a relationship between depressive symptoms and teachers’ high levels of role conflict and role ambiguity [ 15 ] and we expected to uncover new relationships between role problems and HAC; however, no such associations were found in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…Among different professions, doctors are more vulnerable to develop depressive symptoms because of excessive emotional stress of emergency management, critical decision-making, death declaring, demanding patients, work load, duty hours, night shifts, unintentional medical mistakes and lack of sleep etc [10]. The global prevalence of depression among doctors is 10-15% [11,12], while looking over Pakistan, about 25-30% doctors are facing the depressive symptoms [13].…”
mentioning
confidence: 99%